Sung Adornment: Changing Masculinities at Lake Kopiago, Papua New Guinea - Haley, Nicole (The Australian journal of anthropology, 2008)
In the space of 50 years, ideals of masculinity in the western end of the Southern Highlands have been radically transformed. Gone, for instance, is the bachelor cult where young boys were grown into men. Drawing upon ethnographic research undertaken over the past decade, in the Lake Kopiago sub-district in the far north-western corner of Southern Highlands Province, this paper seeks to document these changing masculinities and explore their portrayal by juxtaposing ‘traditional’ and contemporary growth enhancing spells and courting songs—particularly those composed and sung by men. In doing so, this paper also seeks to explore how guns, marijuana, discos and pornographic movies have come to figure centrally in contemporary notions of masculinity. It will also document how the proliferation of marijuana and small arms has transformed young men with otherwise very little standing in the community into self-promoted leaders who have taken it upon themselves to publicly police the sexuality of women in increasingly violent ways.